THE INFLUENCE OF SKILLS AND ATTITUDES ON ENTREPRENEURIAL INTENTIONS: CASE STUDY OF MARANATHA CHRISTIAN UNIVERSITY STUDENTS - Sherren Lias; Henky Lisan Suwarno (UPT Publikasi Ilmiah UNISBA, 2026)
In the era of digital economy and increasingly intense global competition, the development of entrepreneurial intentions among human resources with entrepreneurial potential has become crucial. This study aims to examine the influence of entrepreneurial skills and attitudes on entrepreneurial intention among management students at a private university in Bandung. The research involved 156 respondents selected through purposive sampling and employed a questionnaire using a 5-point Likert scale. Data were processed using Partial Least Squares Structural Equation Modeling (PLS-SEM) and regression analysis. The results indicate that both entrepreneurial skills and entrepreneurial attitudes have a positive and significant effect on entrepreneurial intention. These findings highlight that entrepreneurial skills and attitudes are essential internal factors that influence an individual's intention to start a business. Therefore, internal readiness—shaped by both competence and mindset plays a key role in entrepreneurial decision-making. The study emphasizes the importance of integrating practical skills and reinforcing positive entrepreneurial attitudes within higher education curricula, as these components are instrumental in fostering entrepreneurial intention among students